2015
DOI: 10.1021/acsmacrolett.5b00651
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Side-Chain Modifications of Methionine-Containing Elastin-Like Polypeptides as a Versatile Tool to Tune Their Properties

Abstract: Tuning the LCST of temperature-responsive recombinant elastin-like polypeptides has usually been achieved by designing different protein sequences, in terms of amino acid composition and length, implying tedious molecular cloning steps. In the present work, we have explored the chemoselective alkylation of methionine as a means to modify elastin repeat side chains and modulate the LCST of the polypeptides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(78 citation statements)
references
References 36 publications
(69 reference statements)
2
76
0
Order By: Relevance
“…With these new parent ELP samples in hand, we first sought to prepare methyl sulfonium derivatives of ELP-M-20 and ELP-M-40 as analogs of our previously reported methylated (VPGMG) 20 sample, to study the effects of Met sulfonium "dilution" along the ELP backbone on We previously reported that quantitative methylation of Met residues in (VPGMG) 20 led to a complete loss of the Tt due to introduction of multiple hydrophilic sulfonium groups. 23,24 and can also alter the micellization properties of gemini surfactants.…”
Section: Counterion Exchangementioning
confidence: 99%
See 3 more Smart Citations
“…With these new parent ELP samples in hand, we first sought to prepare methyl sulfonium derivatives of ELP-M-20 and ELP-M-40 as analogs of our previously reported methylated (VPGMG) 20 sample, to study the effects of Met sulfonium "dilution" along the ELP backbone on We previously reported that quantitative methylation of Met residues in (VPGMG) 20 led to a complete loss of the Tt due to introduction of multiple hydrophilic sulfonium groups. 23,24 and can also alter the micellization properties of gemini surfactants.…”
Section: Counterion Exchangementioning
confidence: 99%
“…13 The use of chemoselective reactions to selectively modify specific residues in ELPs post-synthesis has been shown to be a promising means to introduce new functionalities and impart new properties to ELPs, especially at their chain ends, 14,15,16,17 and more scarcely at ELP side-chain residues. 18,19 In a previous study, we reported the chemoselective alkylation of all methionine (Met) residues in the ELP sequence (VPGMG) 20 , which contains Met residues in every repeat, and used this modification to tune the LCST of the resulting polysulfonium ELP derivatives. 20 However, a limitation of this system was the need to use hydrophobic alkylating reagents, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The multiple Met residues were quantitatively alkylated to give uniform sulfonium derivatives whose properties could be tuned by variation of the alkylating groups. 63 Contrary to the broad applicability of Met alkylation to…”
Section: Alkylation Of Thioether Groupsmentioning
confidence: 99%